Potentiometric biosensor based on artificial antibodies for an Alzheimer biomarker detection - Ribeiro, Sónia Claúdia (2022)
This paper presents a potentiometric biosensor for the detection of amyloid β-42 (Aβ-42) in point-of-care analysis. This approach is based on the molecular imprint polymer (MIP) technique, which uses covalently immobilised Aβ-42 to create specific detection cavities on the surface of single-walled carbon nanotubes (SWCNTs). The biosensor was prepared by binding Aβ-42 to the SWCNT surface and then imprinting it by adding acrylamide (monomer), N,N’-methylene-bis-acrylamide (crosslinker) and ammonium persulphate (initiator). The target peptide was removed from the polymer matrix by the proteolytic action of an enzyme (proteinase K). The presence of imprinting sites was confirmed by comparing a MIP-modified surface with a negative control (NIP) consisting of a similar material where the target molecule had been removed from the process. The ability of the sensing material to rebind Aβ-42 was demonstrated by incorporating the MIP material as an electroactive compound in a PVC/plasticiser mixture applied to a solid conductive support of graphite. All steps of the synthesis of the imprinted materials were followed by Raman spectroscopy and Fourier transform infrared spectroscopy (FTIR). The analytical performance was evaluated by potentiometric transduction, and the MIP material showed cationic slopes of 75 mV-decade−1 in buffer pH 8.0 and a detection limit of 0.72 μg/mL. Overall, potentiometric transduction confirmed that the sensor can discriminate Aβ-42 in the presence of other biomolecules in the same solution.